Neonatal Intraventricular Hemorrhage: Current Perspectives and Management Strategies - Felicia H. Z. Chua; Lee Ping Ng; Sharon Y. Y. Low (Encyclopedia)
Neonatal intraventricular hemorrhage is a serious condition associated with significant acute and long-term morbidity and mortality. Neurosurgical intervention aims to relieve life-threatening raised intracranial pressure and prevent neurological deterioration. In recent years, advancements in disease understanding have paved the way for clinicians to re-evaluate conventional approaches in the management of affected patients. Examples include various neurosurgical techniques to actively reduce blood products with a view to avoid the consequences of complex hydrocephalus and intraparenchymal injury in the developing brain. In this entry paper, we aim to provide an overview of the current perspectives, pathophysiology and management strategies for this difficult condition.